Etiology of anemia in primary hypothyroid subjects in a tertiary care center in Eastern India - Chanchal Das; Pranab K Sahana; Nilanjan Sengupta; Debasis Giri; Mukut Roy; Prasanta Mukhopadhyay (Indian Journal of Endocrinology and Metabolism, 2012)
Introduction: The association of anemia with primary hypothyroidism has been common knowledge for many years. However; its pathogenesis is far from clear in many cases. Often the causes of anemia are manifold. Aims and objectives: In this study, we evaluated the causes of anemia in patients with primary hypothyroidism. Materials and Methods : Sixty adult nonpregnant untreated primary hypothyroid patients with anemia without any obvious cause were included. All patients were subjected to full medical history, clinical examination, biochemical and imaging studies. Serum iron profile, vitamin B12, folic acid, anti parietal cell antibody, anti TPO antibody, bone marrow study, and stool for occult blood, Coomb′s test, HPLC for hemoglobinopathies and complete hemogram with reticulocyte count were done and analyzed. Results: Normocytic, normochromic anemia was present in 31 patients (51.6%) followed by microcytic anemia in 26 patients (43.3%). Six patients (10%) had megaloblastic anemia with vitamin B12 deficiency including 3 cases of pernicious anemia. Two patients had combined deficiency of iron and vitamin B12. Conclusion: Normocytic normochromic anemia with normal bone marrow was commonest type of anemia in this study, followed by iron deficiency anemia.